Pengaruh Penggunaan QRIS Sebagai Alat Pembayaran Digital Terhadap Pengelolaan Keuangan Pribadi Karyawan PT.Alkana Diza Nusantara di Era Cashless Society - Dwi Wara Sari; Adria Wuri Lastari; Mulia Inda Purwati (CV. Aksara Global Akademia, 2026)
This study aims to examine the effect of the use of the Quick Response Code Indonesian Standard (QRIS) as part of digital payment instruments on the personal financial management of employees at PT. Alkana Diza Nusantara in the era of a cashless society. The rapid development of financial technology has encouraged a shift in transaction behavior from cash to cashless systems, making it important to understand its impact on individual financial management more comprehensively. This study employs a quantitative approach with a causal associative research design to analyze the relationship between variables. The population consists of 42 employees, with total sampling used as the sampling technique. Data were collected through a Likert-scale questionnaire that had been tested for validity and reliability. Data analysis techniques include classical assumption tests, simple linear regression analysis, t-test, and the coefficient of determination (R²) to measure the extent of the independent variable’s influence on the dependent variable. The results show that the use of QRIS has a positive and significant effect on personal financial management. This is evidenced by a regression coefficient of 0.923 and a significance value of 0.000 (<0.05). Furthermore, the coefficient of determination (R²) of 0.735 indicates that QRIS usage explains 73.5% of the variation in personal financial management, while the remaining 26.5% is influenced by other variables outside the scope of this study. These findings suggest that digital payment usage can enhance the effectiveness, efficiency, and discipline of individual financial management